Áreas verdes urbanas : um estudo de caso em Passo Fundo - RS - Benetti, Lisiane Frosi (2015)
The vegetation of a city plays a central role, considering its ecological, economic, aesthetic and recreational functions. Vegetation and green areas should be used in evaluation of the environmental quality of a city, because of its fundamental importance to the welfare of the people living there, such as shading, filter for sun radiation, air pollution control, many physical and psychological benefits, and other. In spite of the established importance, most Brazilian cities is harmed by low levels of vegetation covering and green areas, as such as the irregular distribution of this. Thus, this study aims to diagnose and quantitatively analyse the vegetation and green areas in Passo Fundo, RS, in order to support questions relating to environmental planning. At first, took place the context and description of the study area, the urban perimeter of the city. After that, vegetation mapping was conducted, from scanning and image interpretation techniques, using, which allowed quantifying vegetation covering, as well as make calculations of percentages and rates of vegetation for the urban perimeter and for individual sectors. The obtained result for percentage of vegetation cover was 31,14% to the city, higher than the minimum recommended of 30%. Then were chosen three different sectors which had their green areas mapped and described in a card, describing particularities of each place, as total surface area, size of vegetation and soil cover, and occupancy characteristics of surrounding areas. Was also calculated green area index, obtaining a result of 0,97 m²/ inhabitant; the index was calculated for the sectors too. The calculated values are far below the minimum recommended by the Brazilian Society of Urban Forestry, and used as pattern to the study, showing the situation in other Brazilian cities, and neglect of environmental quality and life of urban dwellers.